Iatrogenic "aortopulmonary window": percutaneous rescue closure as a bridge to surgical repair. (8th September 2015) - Marini, Davide; Ferraro, Gaetana; Agnoletti, Gabriella
Abstract: We present the case of a 15-year-old boy who underwent arterial switch operation due to transposition of the great arteries with severe scoliosis, obstruction of the right coronary ostium, and severe stenosis of the pulmonary trunk. Balloon angioplasty caused a large aortopulmonary shunt provoking myocardial ischaemia and pulmonary hypertension. The traumatic "aortopulmonary window" was percutaneously occluded using an Amplatzer Septal Occluder device as a bridge to surgical repair.